Pemanfaatan Tongkol Jagung Dan Sekam Padi Menjadi Asap Cair Menggunakan Proses Pirolisis - Elssy, Elisabeth ; Abrina Anggraini, Sinar Perbawani; Yuniningsih, Susy (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Heat exchange causes cold water to change temperature where the cooling water temperature to rise because the resulting heat is carried by a fluid which is absorbed by the water. To overcome that we need some cooling to reduce the temperature of the water is by using a cooling tower. The goal is to find out and determine